2020
DOI: 10.3390/foods9091265
|View full text |Cite
|
Sign up to set email alerts
|

Food Security and Hygiene Practice among Adolescent Girls in Maiduguri Metropolitan Council, Borno State, Nigeria

Abstract: Inadequate food security contributes to poor health outcome for all, including adolescent girls. The study aims at determining the level of food security and hygiene among adolescent girls. A school-based cross-sectional study was carried out among adolescent girls aged 10 to 19 years old from six schools in Maiduguri Metropolitan Council, Borno State. The instrument for data collection was a questionnaire using KoBoCollect Toolbox between June and July 2019. Multivariable logistic regression was used to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 36 publications
1
2
2
Order By: Relevance
“…Surprisingly, household size was not associated with food insecurity, a finding contrary to those in existing literature (Drammeh et al, 2019). It was however similar to findings from previous studies in Maiduguri, northeastern Nigeria (Shapu et al, 2020) and Pakistan (Sheikh et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Surprisingly, household size was not associated with food insecurity, a finding contrary to those in existing literature (Drammeh et al, 2019). It was however similar to findings from previous studies in Maiduguri, northeastern Nigeria (Shapu et al, 2020) and Pakistan (Sheikh et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…The proportion of adolescents who experienced hunger and reported having no food of any kind in the house was quite high, an indication that severe forms of food insecurity and hunger may be more prevalent than is assumed in previous literature (Fraval et al, 2019; Elgar et al, 2021). The proportion was however much lower than findings from previous studies among in-school adolescents in Maiduguri, northern Nigeria (Shapu et al, 2020), Ghana (Seidu et al, 2020; Masa et al, 2021) and Southeast Asian countries (Peltzer & Pengpid, 2017). The observed disparities may be due to the additional stress and disruption of socioeconomic activities caused by insurgency and terrorism in the northeastern parts of Nigeria as well as differences in the measurement scales used.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…In line with previous research in both areas (urban and rural) Rourkela City, Sundargarh District, Odisha which also stated that employment status had no relationship with housewife hygiene practices 17 . Contrary to other results from previous research in Nigeria which revealed that mother's work is related to the level of food security 18 . The conditions found based on the results of the study, both housewives who have other jobs or not, equally apply good food sanitation hygiene.…”
Section: The Relationship Between Working Status and The Use Of House...contrasting
confidence: 93%